2003
DOI: 10.1016/s0014-5793(03)01179-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic regulation of the 6‐phosphofructo‐2‐kinase/fructose‐2,6‐bisphosphatase gene family (PFKFB‐1–4) expression in vivo

Abstract: When oxygen becomes limiting, cells shift primarily to a glycolytic mode for generation of energy. A key regulator of glycolytic £ux is fructose-2,6-bisphosphate (F-2,6-BP), a potent allosteric regulator of 6-phosphofructo-1-kinase (PFK-1). The levels of F-2,6-BP are maintained by a family of bifunctional enzymes, 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB or PFK-2), which have both kinase and phosphatase activities. Each member of the enzyme family is characterized by their phosphatase:kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0
20

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(186 citation statements)
references
References 29 publications
(44 reference statements)
6
160
0
20
Order By: Relevance
“…We examined primary lung fibroblasts and the two resultant cell lines from each strain for the presence of PFKFB1-4 mRNA species by multiplex polymerase chain reaction (PCR) and observed simultaneous expression of all four PFKFB mRNAs (PFKFB1-4) in each of the cell populations (Figure 1b and c). This phenomenon has been previously described in certain transformed cells and whole organs (Minchenko et al, 2003) and these data suggest that all four isozymes may be coordinating to set F2,6BP production. We then examined PFKFB3 protein product expression by Western blot analysis and observed an increase in this enzyme with the introduction of LT and a small increase after H-ras V12 introduction (Figure 1d and e).…”
Section: Pfkfb3 Activity Sets the Intracellular F26bp Concentrationsupporting
confidence: 82%
See 1 more Smart Citation
“…We examined primary lung fibroblasts and the two resultant cell lines from each strain for the presence of PFKFB1-4 mRNA species by multiplex polymerase chain reaction (PCR) and observed simultaneous expression of all four PFKFB mRNAs (PFKFB1-4) in each of the cell populations (Figure 1b and c). This phenomenon has been previously described in certain transformed cells and whole organs (Minchenko et al, 2003) and these data suggest that all four isozymes may be coordinating to set F2,6BP production. We then examined PFKFB3 protein product expression by Western blot analysis and observed an increase in this enzyme with the introduction of LT and a small increase after H-ras V12 introduction (Figure 1d and e).…”
Section: Pfkfb3 Activity Sets the Intracellular F26bp Concentrationsupporting
confidence: 82%
“…Minchenko et al (2003) have demonstrated that hypoxia induces PFKFB3 transcription in various cell types and mouse tissues and that this induction is completely abrogated in mouse embryonic fibroblasts conditionally nullizygous for HIF-1a (Minchenko et al, 2002(Minchenko et al, , 2003. PFKFB3 thus may serve as an essential transcriptional target of HIF-1a and the adaptive response to hypoxia by transformed cells.…”
Section: Discussionmentioning
confidence: 97%
“…Sequence analysis revealed the presence of several putative HREs within the Ϫ3566 nucleotides of the human pfkfb3 promoter, which could explain the described effect of hypoxia on the induction of pfkfb3 gene (11,29). Luciferase expression showed that the two longest constructs (PFKFB3/Ϫ3566 and PFKFB3/Ϫ1407) exerted the maximal hypoxic response, pointing out the major contribution of nucleotides over Ϫ1407 bp.…”
Section: Discussionmentioning
confidence: 88%
“…The postnatal decrease in cardiac HIF signaling therefore leads to downregulation of cardiac Hand1 expression, in turn leading to upregulation of lipid metabolism and lipid oxidation after birth. Several potential metabolic control targets of HIF signaling have been found in skeletal muscle [23], and the expression of some genes encoding glycolytic enzymes in the heart are directly HIF-regulated [24]. It therefore seems likely that HIF signaling has a pivotal (yet incompletely defined) role in the neonatal cardiac metabolic shift.…”
Section: Hif Signalingmentioning
confidence: 99%